A comparison of hepatitis E and A in a teaching hospital in Northwestern Romania. Acute hepatitis E – a mild disease? - Istrate, Alexandru; Rădulescu, Amanda Lelia (Medicine and Pharmacy Reports, 2020)
Background and aims. The incidence of locally acquired hepatitis E has increased in recent years across Europe. There are only few data on hepatitis E in Romania. The purpose of our research was to describe and compare hepatitis E and hepatitis A in adult patients. Methods. We included all consecutive adult patients with hepatitis E and hepatitis A admitted to the Teaching Hospital of Infectious Diseases, Cluj-Napoca, Romania between January 2017 and August 2019. Results. Hepatitis E incidence increased in 2018-2019 compared to 2017. The average age in hepatitis E (n=48) patients was 50.6 versus 39.1 years in hepatitis A (n=152, not including 262 minors) and two-thirds of the patients in both groups were men. Compared to hepatitis A, patients with hepatitis E presented significantly less modified AST and ALT, bilirubin, prothrombin index and INR levels. We found more comorbidities in hepatitis E patients adjusted for age and gender. Severe forms were found in 5 (3.3%) hepatitis A patients, compared to 12 (25%) of hepatitis E patients, of which 3 died. Ribavirin treatment was considered in 9 patients with acute-on-chronic hepatitis E, immunosuppression, cancers or neurological manifestations, showing good results. Conclusions. We observed an increased number of hepatitis E cases. Although laboratory results were less modified compared to hepatitis A, we found a higher number of severe hepatitis E cases. Ribavirin treatment seems to be beneficial in patients with preexisting conditions.